Minocycline markedly reduces acute visceral nociception via inhibiting neuronal ERK phosphorylation - Cho, Ik-Hyun (BioMed Central, 2012)
BACKGROUND: Minocycline prevents the development of neuropathic and inflammatory pain by inhibiting microglial activation and postsynaptic currents. But, how minocycline obviates acute visceral pain is unclear. The present study investigated whether minocycline had an any antinociceptive effect on acetic acid-induced acute abdominal pain after intraperitoneal (i.p.) administration of saline or minocycline 1 hour before acetic acid injection (1.0%, 250 μl, i.p.). RESULTS: Minocycline (4, 10, or 40 mg/kg) significantly decreased acetic acid-induced nociception (0-60 minutes post-injection) and the enhancement in the number of c-Fos positive cells in the T5-L2 spinal cord induced by acetic acid injection. Also, the expression of spinal phosphorylated extracellular signal-regulated kinase (p-ERK) induced by acetic acid was reduced by minocycline pre-administration. Interestingly, intrathecal introduction of PD98059, an ERK upstream kinase inhibitor, markedly blocked the acetic acid-stimulated pain responses. CONCLUSIONS: These results demonstrate that minocycline effectively inhibits acetic acid-induced acute abdominal nociception via the inhibition of neuronal p-ERK expression in the spinal cord, and that minocycline may have therapeutic potential in suppressing acute abdominal pain.